Strategi Pemenangan Tamizi Pada Pemilu Serentak Tahun 2024 - Gebrina Riska; Ubaidullah Ubaidullah; Khalisni Khalisni; Reza Fahlevi (Jurnal Realitas Sosial, 2025)
The concept of a winning strategy in electoral politics refers to a systematically designed and strategically implemented plan developed by legislative candidates and their campaign teams to secure electoral victory.This study investigates the political strategy employed by Tarmizi, a candidate from the Aceh Party, during the 2024 simultaneous legislative elections for the Aceh Provincial House of Representatives (DPRA) in Electoral District 10. Tarmizi successfully secured a DPRA seat for the 2024–2026 term, with a remarkable 100% increase in votes compared to the previous election, reaching a total of 20,928 votes. The purpose of this research is twofold: first, to analyze the strategic approach adopted by Tarmizi in the DPRA legislative contest of 2024; second, to identify the key political factors influencing his electability. Employing a qualitative-descriptive research design, data were collected through in-depth interviews, field observations, and document analysis. The study is grounded in political marketing theory, Peter Schroder’s political strategy framework, and the concept of political positioning. The findings reveal that Tarmizi’s campaign strategy was primarily characterized by a political marketing approach, specifically push marketing techniques emphasizing social engagement and grassroots outreach. His electoral success was significantly influenced by his established political track record, endorsement from influential religious figures, a trustworthy and socially engaged public persona, and an effective issue-based positioning strategy that resonated with voters, particularly on socio-political concerns cultivated since his previous term.